SME Digital Transformation as a Post-Pandemic Recovery Facility in Pekalongan Indonesia - Henny Diana Erlany; Fania Mutiara Savitri; Ngatno Ngatno; Bulan Prabawani; Widiartanto Widiartanto (Universitas Serambi Mekkah, 2022)
Digital transformation is a new trend in the Industrial Age 4.0, leading to a new business pattern called the digital economy which is exacerbated by the crisis due to the Covid-19 pandemic. However, MSME actors in Indonesia face obstacles in carrying out the business transformation process, because 90% of Indonesian MSMEs are still run conventionally due to problems regarding the unpreparedness of resources. Therefore this study aims to find out and analyze the main achievement goals for SMEs so that they can continue to provide good performance after the Covid-19 pandemic in Pekalongan City and to know and analyze how digital transformation is a means of recovery for SMEs after the Covid-19 pandemic in Pekalongan City. This study uses a qualitative method with a phenomenological approach where data is collected by distributing questionnaires to MSME actors in Pekalongan. In the data collection process, this study involved several informants by conducting in-depth interviews, policy analysis, and documentation as supporting data. Apart from involving MSE actors in various fields, this research also involved informants who know the dynamics of MSMEs in Pekalongan City. Head of the Pekalongan City Trade, Cooperative and UKM Office, Chair of the Pekalongan City UMKM Association, and Head of the Pekalongan City Shopee Market Place. The results of the study show that the main achievement target for SMEs in order to continue to provide good performance after the Covid-19 pandemic in Pekalongan City is to achieve a sustainable competitive advantage. Then digital transformation becomes an alternative solution in post-pandemic recovery. The policy implications are expected that MSEs will make marketing innovation a priority for MSMEs by combining online and offline marketing, implementing e-commerce systems and collaborating with related parties in overcoming obstacles and obstacles in the adaptation process. Keywords: Digital transformation, recovery, MSEs, Pandemic